PENGGUNAAN MEDIA INTERNET DENGAN MOTIF KREATIF DAN HUBUNGANNYA DENGAN KARAKTER PESERTA DIDIK - Sofyan, Edy; Pandikar, Ernandia (STKIP Subang, 2020)
The internet can have a positive impact on its users if its use is based on good values ​​and ethics. However, at this time there has been a tendency to ignore values ​​and ethics by Internet users because Internet media users can browse whatever they want and will experience realities beyond what they do everyday so they tend to ignore the existing character structures, value systems and norms. agreed upon in the community.The general objective to be achieved in this study is to describe and analyze the relationship between the use of internet media and creative motives for the character of students in public high schools in Bandung. The approach used in this research is a quantitative approach with a survey method. The population is students of class XI SMA Negeri in the city of Bandung. Determination of the research sample using multi stage random sampling as many as 159 students. Data collection used a questionnaire and analyzed using correlation and regression analysis. Based on data processing and analysis, research results that describe; There is a relationship between the use of internet media and creative motives on the character of students by 31.1%, while the rest is influenced by other factors which are not examined in this study. The use of internet media with creative motives has a positive relationship and influence on efforts to build the character of students in schools, so it is recommended that civic education teachers need to direct and guide students to be wiser in using internet media.